Human development and distance education: how are interactivity and interaction articulated? - Vasconcelos, Ivar Cesar Oliveira de [UNESP] (2011)
Currently the achievements of technology have not been enough to overcome the misery, in which are numerous human groups. Relegated to its background, the human being sees those scenarios, which brings out discussions about its formation, in which values are regarded as the scientific and technological aspects. The educational research inspired by this framework involving the theme of human development, update and re-frame concepts related to the linkage between interactivity and interaction, two important features presented in the process of Distance Education (DE). The research inquired about how these features have been articulated. It conducted a field study in which two professors were interviewed. The results showed that the integration between interactivity and interaction, involving aspects such as autonomy, critical awareness, relationships among students, the sharing of values and worldviews, is at the base of the educational processes of the DE. They also showed that, on these processes, there are shortcomings regarding the development of values and having to be thought the tutor training strategies from an interdisciplinary view.